Sexual and Relationship Satisfaction: the role of perceived (non)problematic sexual desire discrepancy in gay and heterosexual men - Pereira, Tiago Jose (2019)
Sexual desire discrepancy has been associated with sexual and relationship dissatisfaction. Nonetheless, little is known regarding the role of desire discrepancy in gay men, as main research has been systematically conducted with heterosexual couples. Also, only one study has focused on problematic sexual desire discrepancies and sexual satisfaction with lesbian women. This study sought to understand if perceived sexual desire discrepancy influences sexual and relationship satisfaction in men, and to explore differences according to sexual orientation. A total of 346 men (245 heterosexual and 101 gay) completed an online survey and answered sociodemographic questions, a specific question about sexual desire discrepancy, and completed the Global Measure of Sexual Satisfaction and the Global Measure of Relationship Satisfaction. The main findings showed differences in sexual and relationship satisfaction according to sexual desire discrepancy groups, with men who experienced no desire discrepancy being more satisfied within their relationship and sex life compared to men who experienced both problematic and nonproblematic sexual desire discrepancy. Additionally, men who experienced nonproblematic sexual desire discrepancy reported being more sexually and relationship satisfied than men who experienced problematic sexual desire discrepancy. No sexual orientation differences were found. Overall, current findings emphasize the role of (non)problematic desire discrepancy in sexual and relationship satisfaction among heterosexual and gay men.